3D nonlinear transient field‐circuit modeling of inductive fault current limiters. (18th June 2015) - Cvoric, Dalibor; Lahaye, Domenico; de Haan, Sjoerd; Ferreira, Braham
Summary: Due to increasing levels of fault currents, fault current limiters (FCLs) are expected to play an important role in the protection of future power grids. Inductive saturable FCLs are particularly interesting due to their inherent reaction on the fault. Many different configurations have been proposed in literature. Being difficult or impossible to create accurate analytical models of some FCL configurations, the development of finite element (FE) models for inductive FCLs is required. This paper presents a 3D nonlinear transient FE modeling technique applied to two inductive FCLs, namely the so‐called open‐core and three‐leg single‐core FCLs. The models have been validated by comparing simulation results with lab measurements. Results show excellent agreement. The models constitute a valuable tool for design, optimization, and verification of inductive FCLs. Copyright © 2015 John Wiley & Sons, Ltd.